Modeling, Analysis and Control of Different DC-DC Converter Topologies for Photovoltaic Emulator - Mohammad Tauquir Iqbal; Mohd Tariq (International Journal of Applied Power Engineering (IJAPE), 2017)
This paper presents the modeling, analysis and control of different DC-DC converter topologies to emulate the photovoltaic (PV) system. A PV emulator is basically a DC-DC converter having same electrical characteristics that of solar PV panel. The emulator helps to achieve real characteristics of PV system in a better way in an environment where using actual PV systems can produce inconsistent results due to variation in weather conditions. The paper describes different types of DC-DC converters like buck, Resonant and Quasi Resonant Converter. The complete system is modelled in MATLAB® Simulink SimPowerSystem software package. The Simulation results obtained from the MATLAB® Simulink SimPowerSystem software package for different topologies under steady and dynamic conditions are analyzed and presented. An evaluation table is also presented at the end of the paper, presenting the effectiveness of each topology.